2013
DOI: 10.1371/journal.pone.0066139
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Tolerance in a Mouse Model of Sidt2 Deficiency

Abstract: Sidt2 was identified as a novel integral lysosomal membrane protein recently. We generated global Sidt2 knockout mice by gene targeting. These mice have a comparatively higher random and fasting glucose concentration. Intraperitoneal and oral glucose tolerance tests in Sidt2 knockout mice indicated glucose intolerance and decreased serum insulin level. Notably, the Sidt2−/− mice had hypertrophic islets compared with control mice. By Western blot and immunofluorescence, Sidt2−/− mouse islets were shown to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…In planaria, silencing in response to ingested dsRNA can occur in most tissues (Rouhana et al, 2013) and weak homologs of SID-1 are present (Zayas et al, 2005) but the roles of these homologs in the uptake of dsRNA are yet to be evaluated. Finally, a mammalian homolog of SID-1, SidT2, is a lysosomal membrane protein (Jialin et al, 2010), which is in contrast to the reported plasma membrane localization of C. elegans SID-1 (Winston et al, 2002), and mouse knockouts of SidT2 have impaired glucose tolerance (Gao et al, 2013), which is in contrast to the lack of obvious defects in C. elegans that lack SID-1 (Winston et al, 2002), suggesting that SID-1 and its mammalian homologs also have alternative function(s). An intriguing clue to such alternative functions comes from a close inspection of sequence similarity, which suggests that both SID-1 and CHUP-1 have a domain with weak similarity to hydrolases (Pei et al, 2011).…”
Section: Import Into Cellsmentioning
confidence: 99%
“…In planaria, silencing in response to ingested dsRNA can occur in most tissues (Rouhana et al, 2013) and weak homologs of SID-1 are present (Zayas et al, 2005) but the roles of these homologs in the uptake of dsRNA are yet to be evaluated. Finally, a mammalian homolog of SID-1, SidT2, is a lysosomal membrane protein (Jialin et al, 2010), which is in contrast to the reported plasma membrane localization of C. elegans SID-1 (Winston et al, 2002), and mouse knockouts of SidT2 have impaired glucose tolerance (Gao et al, 2013), which is in contrast to the lack of obvious defects in C. elegans that lack SID-1 (Winston et al, 2002), suggesting that SID-1 and its mammalian homologs also have alternative function(s). An intriguing clue to such alternative functions comes from a close inspection of sequence similarity, which suggests that both SID-1 and CHUP-1 have a domain with weak similarity to hydrolases (Pei et al, 2011).…”
Section: Import Into Cellsmentioning
confidence: 99%
“…−/− mice were generated as previously described (21). All mice were housed with standard temperature and humidity and were maintained on a 12 h light/dark cycle.…”
Section: Sidt2mentioning
confidence: 99%
“…Generation of the Sidt2 −/− mice was described previously (Gao et al 2013). All mice were housed in Animal Laboratory Center at Xinhua hospital, Shanghai, China.…”
Section: Animalsmentioning
confidence: 99%
“…Five-micrometer paraffin-embedded pancreas sections were stained as described previously (Gao et al 2013). Isolated primary β-cells were fixed with 4% paraformaldehyde for 20 min, permeabilized for 20 min in 0.2% Triton X-100 buffer, blocked with PBS containing 5% BSA, and subjected to double immunofluorescence staining.…”
Section: Immunofluorescence Staining On Pancreas Sections and Isolatementioning
confidence: 99%
See 1 more Smart Citation